Analisis Kemampuan Konsep Dasar Pengukuran pada Siswa Kelas 1 SD - M. Dian Sidik; Salmaini Safitri Syam; Chandra Chandra (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2025)
Measurement is an essential part of learning. It involves comparing an object with certain criteria or measures. In the context of education, measurement helps educators to understand the level of student achievement of the learning objectives that have been set. This study aims to analyze the ability of grade I elementary school students to understand the basic concepts of measurement, both from the cognitive, psychomotor, and affective aspects. Data collection was carried out through assessment instruments in the form of multiple choice questions and short fillings, practical activities using measuring instruments, and attitude observations during the learning process. The results showed that most students had understood the basic concepts of measuring standard and non-standard units, although there were still some errors in unit conversion and accuracy in measurement practices. This finding is an important basis for developing more contextualized and interactive measurement learning in the early grades of elementary school.